G427 Improving documentation and clinical practice in the 6–8 week baby check in uk general practices. (27th April 2015) - Wilson, IE; Kaushik, N; Frank, TL
Abstract : Infants require a full physical examination within 72 h of birth and again between 6–8 weeks of age. NICE Clinical Guideline CG37 titled 'Routine postnatal care of women and their babies' specifies a 43-part list of expected examination points. We wanted to determine the proportion of infants attending for their 8–week baby check at a local General Practice, who had adequate documentation of examination findings in the electronic health records (EHR). The audit also aimed to determine if practice could be improved using an online template. A retrospective audit assessing documentation of examination findings for the 8-week check was performed on 20 patients attending the practice during a four-month period. 100% babies at the 6–8 week check should have all 43 criteria entered into the EHR. Each patient was given a score relating to the number of criteria documented. We then created a unique, easily identifiable '8–week baby check' electronic template for use with the EHR and doctors in the practice were trained in its use. Subsequent re-audit on a sample of 20 patients completed the audit cycle. The initial audit showed overall percentage documentation was 22%, well below the 100% standard. Best recorded were the red–reflex, heart sounds and hips, entered for 11 of 20 patients. 0 of 20 patients records commented on hands, feet, nose, ears, neck or presence of dysmorphism. 8 patients had only '8-week check OK' entered into the EHR. Re–audit once the electronic template was in place showed a 73% improvement in documentation, with all 43 criteria being entered for at least 95% of the children. The initial audit highlighted inadequate documentation of examination findings in the EHR at the 6–8 week newborn check. A well-designed intervention was shown to significantly improve practice thus maintaining medico-legally sound patient notes and optimising patient safety, as the template ensures comprehensive examinations are performed. With increasing shifts towards paperless advanced software systems, there are ample opportunities to improve the quality of care and documentation.